Numerical modelling of vibro-acoustic problem in presence of uncertainty: Application to a vehicle cabin. (15th January 2019) - Dammak, K.; Koubaa, S.; El Hami, A.; Walha, L.; Haddar, M.
Abstract: In this paper, the formulation of the finite element method for vibro-acoustic problem is applied to a vehicle to investigate the sound pressure level inside the cabin. This study is combined with a stochastic analysis to account for variability of different parameters, considered as random variables, which are related to the characteristics of materials and boundary conditions. The results show that the Generalized Polynomial Chaos (gPC) method is more efficient compared to the direct Monte Carlo simulation (MC) without causing significant loss of accuracy. It is also shown that uncertainty levels in the input data could result in large variability in the calculated interior sound pressure level. The result of this modeling strongly depends on the order of the Polynomial Chaos. An increase in this order is accompanied by a better projection of the solution.